Robust modeling, analysis and optimization of entrained flow co-gasification of petcoke with coal using combined array design. (1st January 2020) - Zhang, Jinchun; Hou, Jinxiu; Feng, Zhongwei; Zeng, Qiang; Song, Qinghua; Guan, Shiheng; Zhang, Zichuan; Li, Zhaoqian
Abstract: This study is focused on robust modeling, analysis and optimization of entrained flow co-gasification of petcoke with coal, which is very important to the stable operation of this process as well as downstream processes. Unlike general robust modeling method that traditional Taguchi's crossed array design is applied, combined array design was used in this study. Then based on the exiting general experiments and the constructed robust models, a systematic investigation was conducted into the effects exerted by oxygen and steam concentrations (OC and SC) not only on the mean but also on the variance of H2, CO and (H2 + CO) production. Finally, the co-gasification process was robustly optimized. The result reveals that the average production of H2, as well as that of (H2 + CO), rises with OC increasing but declines with SC increasing. Moreover, higher OC inhibits the fluctuations in H2 and (H2 + CO) production, while higher SC makes their fluctuations more notable. The robust optimization solutions of OC and SC are observed to be 1.56% and 50%, respectively. Graphical abstract: Image 1 Highlights: Robust model for entrained flow co-gasification of petcoke and coal was built. Combined array design was used to build the robust model. Some controllable operating parameters were robust assessed systematically. The entrained flow co-gasification of petcoke and coal was robust optimized.